Gradual release of nicotine in smoking cessation treatment: Patches and chewing gum (Research, Society and Development, 2025)
Smoking remains one of the main public health problems, responsible for a high number of preventable deaths and chronic diseases. Although the World Health Organization's global report (2025) points to a significant reduction in the number of smokers in recent decades, about one in five adults is still dependent on cigarettes. This study aimed to conduct a narrative literature review on nicotine replacement therapies and their effectiveness in treating tobacco dependence. The research was conducted in October 2025, using the Google Scholar, SciELO, Capes Journals, and PubMed databases, using the descriptors "Smoking," "Nicotine replacement therapy," "Pharmacological treatment," and "Tobacco control." Articles published between 2020 and 2025 were included, totaling 20 studies analyzed. The results showed that nicotine dependence involves complex neurobiological mechanisms mediated by the release of dopamine and serotonin, making smoking cessation difficult. Nicotine replacement therapies (NRT), especially transdermal patches, chewing gum, and lozenges, have proven effective in reducing withdrawal symptoms and increasing cessation rates, particularly when combined with psychological support and professional follow-up. It is concluded that technological advancements in controlled-release systems, such as matrix and reservoir patches, have improved therapeutic efficiency and adherence to treatment, maintaining stable serum levels and reducing relapses. Therefore, the evolution of these formulations represents an important strategy in the fight against smoking and reinforces the relevance of public policies aimed at tobacco cessation.